PHYLOGENETIC ANALYSIS OF BOVINE Leptospira ISOLATES - Balakrishnan, G; Roy, Parimal; Kirubharan, J JOhn (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Leptospira isolates obtained from bovines were subjected to phylogenetic analysis by sequencing 16s rRNA gene of Leptospira. The phylogenetic analysis of the 16s rRNA of 9 isolates were grouped into three clusters. Partial sequence analysis of 16s rRNA of the isolates revealed that they were having 99.30 to 100.00 per cent identity among the australis isolates with reference strain, Australis australis Ballico. The Leptospira ballum isolate showed 99.70 per cent identity with reference strain and also encompassed with Leptospira hebdomadis isolates and some of the Leptospira australis isolates.